Aсtive electro-optical system for target detection with dynamic spectral processing of optical radiation - Kupchenko, L.F.; Karlov, V.D.; Rybiak, A.S.; Goorin, О.А.; Ponomar, А.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
The issues discussed in this paper provide for further development of studies in the sphere of imaging spectroscopy and laser vision. In terms of forming the information fields (radiation fields), the electro-optical systems are subdivided into the passive and active ones. Passive electro-optical systems use the information fields formed by natural radiation sources, whereas the active ones suggest using artificial sources. Comparative analysis of mathematical and physical issues of designing the electro-optical systems with dynamic spectral processing of optical radiation of the passive and active types has been performed. It has been shown that the controlled dynamic spectral processing of optical radiation can be implemented within the passive and active electro-optical systems on the basis of the same algorithm that represents the operation of the optical processor performing the mathematical operation of dot product. The authors have developed the block diagram of an active electro-optical system with dynamic spectral processing. The algorithm for optimal detection of optical signals has been developed using the basics of signal detection theory. Mathematical modeling of target detection against an inhomogeneous background has been performed. It has been shown that the optimal dynamic spectral processing of optical radiation in an active electro-optical system enables the separation of the desired optical signal by suppressing the background signal. У статті розглянуто дослідження в області спектральної обробки зображень та лазерного бачення. За характером формування інформаційних полів (полів випромінювання) оптико-електронні системи можна поділити на пасивні та активні. Пасивні оптико-електронні системи використовують інформаційні поля, які формуються природними джерелами випромінювання, а активні передбачають використання штучних джерел. Проведено порівняльний аналіз математичних та фізичних аспектів побудови оптико-електронних систем з динамічною спектральною обробкою оптичного випромінювання пасивного та активного типів. Показано, що керована динамічна спектральна обробка оптичного випромінювання реалізується у пасивних та активних оптико-електронних системах за одним і тим самим алгоритмом, який представляє собою роботу оптичного процесора, що виконує математичну операцію скалярного множення вектора на вектор. Розроблено структуру схеми активної оптико-електронної системи з динамічною спектральною обробкою. Із використанням основних положень теорії детектування сигналів розроблено алгоритм оптимального виявлення оптичних сигналів. Проведено математичне моделювання процесу виявлення об’єкта на неоднорідному фоні. Показано, що в результаті оптимальної динамічної спектральної обробки оптичного випромінювання в активній оптико-електронній системі вдалося виокремити корисний оптичний сигнал, повністю заглушивши при цьому сигнал фону.